A TNF Block Genotype may Influence CMV Retinitis in HIV Patients without Affecting Systemic Viral Replication - Edwar, Lukman; Ha, Phuongnhi; Ariyanto, Ibnu A.; Estiasari, Riwanti; Sitompul, Ratna; Lee, Silvia; Price, Patricia (Current HIV Research, 2021)
Background: A conserved TNF block haplotype marked by the minor alleles of rs1800629 (TNFA-308*A) and rs9281523 [BAT1(intron 10)*C] has been linked with several immunopathological conditions and with rapid progression of HIV disease. Reported associations with cytomegalovirus (CMV) retinitis in HIV patients before or during early antiretroviral therapy (ART) may therefore reflect greater replication of CMV in advanced HIV disease or an immunopathological response to CMV in the retina. Objective: As all Indonesian HIV patients display high levels of CMV replication, we evaluated whether TNF block genotypes alter markers of their burden of CMV and/or associate with retinitis. Methods: We assessed 79 consecutive HIV patients beginning ART, 25 HIV patients with a history of CMV-retinitis and 63 healthy adults. HIV RNA, CD4 T-cell counts, CMV-reactive antibody and CMV DNA were measured and alleles of TNFA-308, BAT1(intron 10) and TNFA-1031 (rs1799964) were determined. Results: TNFA-308 and BAT1(intron 10) were in complete linkage disequilibrium. Patients carrying minor alleles at both loci had higher levels of CMV-reactive antibody after one month on ART (p=0.01), but not at other time points spanning 1 year on ART. 50% of patients had detectable CMV DNA before ART, irrespective of TNF block genotypes. However, the TNFA-308*A/- BAT1(intron 10)*C haplotype was more common in CMV-retinitis patients than other patients or healthy controls (p<0.01). Conclusion: The TNFA-308*A/BAT1(intron 10)*C haplotype appears to affect CMV-induced pathology rather than CMV replication.
Keywords: retinitis